Solution to Using mathematical induction, prove that for every positive integer n, 1 · 2 + 2 … - Sikademy
Author Image

Archangel Macsika

Using mathematical induction, prove that for every positive integer n, 1 · 2 + 2 · 3 + · · · + n(n + 1) = (n(n + 1)(n + 2)) / 3

The Answer to the Question
is below this banner.

Can't find a solution anywhere?

NEED A FAST ANSWER TO ANY QUESTION OR ASSIGNMENT?

Get the Answers Now!

You will get a detailed answer to your question or assignment in the shortest time possible.

Here's the Solution to this Question

Base step

for n=1: 1*2=\frac{1*2*3}{3}=2. The statement holds.

Inductive step

Assume that for n=k: 1*2+2*3+...+k(k+1)=\frac{k(k+1)(k+2)}{3}

Then, for n=k+1: 1*2+2*3+...+k(k+1)+(k+1)(k+2)=\frac{k(k+1)(k+2)}{3}+(k+1)(k+2)=

=(k+1)(k+2)(\frac{k}{3}+1)=\frac{(k+1)(k+2)(k+3)}{3}

That is, the statement for n=k+1 also holds true.

Since both the base step and the inductive step have been proved as true, by mathematical induction the statement holds for every natural number n.


Related Answers

Was this answer helpful?

Join our Community to stay in the know

Get updates for similar and other helpful Answers

Question ID: mtid-5-stid-8-sqid-1258-qpid-996